GANGUBAI KATHIAWADI (2022): THE EMPOWERING RESISTANCE - Kulaya Pongpan (Universitas Negeri Yogyakarta, 2023)
The paper argues that we can view the filmic representation of Gangubai Kathiawadi (2022) as a symbolic 'empowering resistance' to injustice in forced prostitution in Asia. The analysis relies on an empowering feminist point of view throughout an investigation of film elements of narration, language use (as translated into English), and symbolization. The paper demonstrates that the resistance is based on three reasons: (1) Depictions of traumatic realities in prostitution with four factors related to India's prostitution, (2) Representation of the objectification of female bodies observed through Catherine Barry's four stages of dehumanization in prostitution, and (3) Portrayal of Gangubai as a moral character, being a virtuous leader and mother figure, which contradicts her conceived social stigmas as a 'devalued prostitute' and the underworld 'Mafia Queen of Mumbai.' Adding to the study, the symbolic analysis reveals that the representation of the color 'white' signifies the character's morality and purity, highlighting her position as an alleged victim. Furthermore, the color endorses a resisting message against prejudice against women in prostitution. The study sheds light on the social conduct of female prostitution that traumatizes women. Most importantly, it offers an alternative interpretation of the representation of a prostitute character, not as a woman in vulnerability, but as a victorious powerful feminist figure.